Corrective Feedback: How has it been implemented in EFL Writing Class? - Megawati, Fika; Kadarisman, A. Effendi; Agustina, Sheila (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
Studies have shown that during the process of Interlanguage development, language learners cannot avoid making grammatical errors in either spoken or written form. Although it is considered as a normal phase, errors can lower students' confidence to be active EFL learners in the class. Accordingly, they need teachers’ appropriate corrective feedback (CF) to produce effective communication in the target language. Thus, considering the significant contribution of grammar knowledge and teachers' feedback on students' English proficiency, this paper aims to explore the perception of 12 EFL teachers’ practices and 91 students, both of whom are involved in an English writing class, about CF. The instruments used to collect the data was closed- and open-ended questionnaire. The results indicate that teachers vary their CF in terms of frequency and types. In addition, students show a different perspective on the effectiveness of CF in writing class. Also, teachers need to become more familiar with electronic CF in order to implement it better in class including for writing instruction process and promoting peer corrective feedback. In line with these findings, suggestions for future research are provided.